Managerial reputation and divisional sell-offs: A model and empirical test - Guedes, Jose; Parayre, Roch (Journal of Banking & Finance, 1997)
This paper presents a reputation model of divestiture activity that yields a sharp cross-sectional implication for event studies of sell-off announcements: A decision to divest a division that is known to be successful conveys good news about the division; in contrast, a decision to divest a division that is known for underperformance conveys no news about the division. We test these hypotheses on a sample of sell-off announcements for which we find stories in the Wall Street Journal unambiguously characterizing the division being sold as either a “winner” or a “loser”. The stock price reaction to the sell-off of losers is indistinguishable from zero while the stock price reaction to the sell-off of winners is a statistically significant 2.5%. These results are strengthened when we expand the sample to include divisions whose profitability was announced in the company's annual report. For this expanded sample, the average stock price reaction to the announcements of sell-offs of losers remains indistinguishable from zero, while returns from the sell-offs of winners average a highly significant 3.4%.